2005
DOI: 10.1152/japplphysiol.01400.2004
|View full text |Cite
|
Sign up to set email alerts
|

Exercise within lower body negative pressure partially counteracts lumbar spine deconditioning associated with 28-day bed rest

Abstract: . Exercise within lower body negative pressure partially counteracts lumbar spine deconditioning associated with 28-day bed rest. J Appl Physiol 99: 39 -44, 2005. First published March 10, 2005; doi:10.1152/japplphysiol.01400.2004.-Astronauts experience spine deconditioning during exposure to microgravity due to the lack of axial loads on the spine. Treadmill exercise in a lower body negative pressure (LBNP) chamber provides axial loads on the lumbar spine. We hypothesize that daily supine LBNP exercise helps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 22 publications
10
80
1
Order By: Relevance
“…Supine treadmill exercise within LBNP effectively mitigated bone loss and changes in bone metabolism associated with simulated microgravity in men [9,36], and while the results from women in the present study were not as consistent as those for men, similar trends existed. Femoral shaft and total hip BMD in the CON group was lower after bed rest than at baseline, but in the EX group there were no differences after bed rest.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Supine treadmill exercise within LBNP effectively mitigated bone loss and changes in bone metabolism associated with simulated microgravity in men [9,36], and while the results from women in the present study were not as consistent as those for men, similar trends existed. Femoral shaft and total hip BMD in the CON group was lower after bed rest than at baseline, but in the EX group there were no differences after bed rest.…”
Section: Discussioncontrasting
confidence: 61%
“…We have previously published reports [9,19,28,36,49] of a study with male subjects in which we used procedures identical to those used for the study reported here. Although in this report we compare the data from female subjects with data from male subjects published earlier [36,49], none of the data from female subjects, nor the heritability data for men or women, have been published previously.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, IVD swelling in spaceflight can be inferred from increases in spine length [5] and body height [6] during spaceflight and from IVD swelling observed in vivo following bed rest (Fig. 2) for a few hours [7,8], overnight [9][10][11][12], and for a number of weeks [13][14][15][16][17][18][19]. At the end of overnight bed-rest, lumbar intradiscal pressure is increased [20].…”
Section: What Are the Likely Mechanisms?mentioning
confidence: 99%